2003
DOI: 10.1590/s0100-06832003000600002
|View full text |Cite
|
Sign up to set email alerts
|

O tráfego de máquinas agrícolas e as propriedades físicas, hídricas e mecânicas de um Latossolo dos Cerrados

Abstract: RESUMONo Brasil, o tráfego contínuo e inadequado de rodados de máquinas e a ação da soleira dos implementos sobre áreas agrícolas na região dos Cerrados têm provocado alterações dos atributos físicos e mecânicos dos solos. Com este entendimento, este estudo teve por objetivo avaliar a influência do rodado traseiro e da soleira de implementos agrícolas, usualmente utilizados na região dos Cerrados, sobre a compressibilidade de um Latossolo Vermelho distrófico típico. Os ensaios foram realizados em parcelas prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
26

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 12 publications
2
10
0
26
Order By: Relevance
“…The scheduling of this traffic would contribute to minimize soil compaction, and consequently, the losses of productivity . Thus, it is important to determine the soil bearing capacity as a function of soil moisture, and to quantify the damages caused to soil structure, when applied pressures exceed the soil bearing capacity (Dias Junior & Pierce, 1996;Oliveira et al, 2003;Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The scheduling of this traffic would contribute to minimize soil compaction, and consequently, the losses of productivity . Thus, it is important to determine the soil bearing capacity as a function of soil moisture, and to quantify the damages caused to soil structure, when applied pressures exceed the soil bearing capacity (Dias Junior & Pierce, 1996;Oliveira et al, 2003;Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Essa degradação na estrutura é agravada, quando as operações de preparo de solo e tráfego de máquinas nas lavouras são realizadas em solos com consistência plástica associadas a pressões superiores à pressão de pré-consolidação (Figueiredo et al, 2000;Silva et al, 2000;Silva et al, 2003). Por outro lado, a redução do tráfego de máquinas e do revolvimento do solo, associado ao uso de plantas de cobertura, pode preservar e até mesmo recuperar a estrutura do solo, mantendo, desta forma, o sistema agrícola mais produtivo (Bragagnolo & Mielniczuk, 1990).…”
Section: Introductionunclassified
“…In clayey Dystroferric Red Latosol with reduced tillage and CT, Argenton et al (2005) reported there were increased soil bulk densities between 71 and 86% for depths ranging from 0.05 to 0.10 m, and between 10 and 16% for depths ranging from 0.30 to 0.40 m. Machine use and unsuitable soil moisture conditions lead to permanent damage to the soil structure (Dias Junior and Pierce, 1996). This is the result of the pressure applied to the ground surface (Argenton et al, 2005) by tires or active parts of the equipment that exceed the soil's ability to withstand the weight (Silva et al, 2003). Such heavy weights are transmitted to various depths through stress distribution (Araujo-Junior et al, 2011).…”
Section: Resultsmentioning
confidence: 99%